1995
DOI: 10.1115/1.2794204
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of Airflow in the Human Nasal Cavity

Abstract: An anatomically correct finite element mesh of the right human nasal cavity was constructed from CAT scans of a healthy adult nose. The steady-state Navier-Stokes and continuity equations were solved numerically to determine the laminar airflow patterns in the nasal cavity at quiet breathing flow rates. In the main nasal passages, the highest inspiratory air speed occurred along the nasal floor (below the inferior turbinate), and a second lower peak occurred in the middle of the airway (between the inferior an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

32
247
1
8

Year Published

1999
1999
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 321 publications
(288 citation statements)
references
References 17 publications
32
247
1
8
Order By: Relevance
“…Despite the small difference in area coverage, region D in the left cavity exhibits a small constricting section which causes a higher resistance in the flow and hence the smaller proportion of airflow through sections C, D and E. The flow in the left cavity stays close to the wall and its distribution is mainly in the middle sections and more dominant in the lower sections, while a small percentage (11.6%) is found in the upper section. This pattern was also observed in the work by Hahn, Scherer and Mozell (1993) and in the model of Keyhani, Scherer and Mozell (1995). In the right cavity the flow is concentrated within the middle sections.…”
Section: Flow Analysis and Heat Transfer In The Turbinate Regionsupporting
confidence: 64%
See 1 more Smart Citation
“…Despite the small difference in area coverage, region D in the left cavity exhibits a small constricting section which causes a higher resistance in the flow and hence the smaller proportion of airflow through sections C, D and E. The flow in the left cavity stays close to the wall and its distribution is mainly in the middle sections and more dominant in the lower sections, while a small percentage (11.6%) is found in the upper section. This pattern was also observed in the work by Hahn, Scherer and Mozell (1993) and in the model of Keyhani, Scherer and Mozell (1995). In the right cavity the flow is concentrated within the middle sections.…”
Section: Flow Analysis and Heat Transfer In The Turbinate Regionsupporting
confidence: 64%
“…It was found that the projection of the inferior turbinates was the only significant parameter and that a greater projection of the inferior turbinate bone laminated the flow by simply decreasing the cross-sectional area of the passageway while larger passageways, with a greater hydraulic diameter, would experience more turbulent flow. The increase in computational power has allowed many numerical simulations, including the pioneering work of Keyhani, Scherer and Mozell (1995) among others. Without considering humidity and water exchange, Lindemann et al (2004) numerically simulated the temperature distribution during inspiration in an anatomically realistic nasal cavity.…”
Section: Introductionmentioning
confidence: 99%
“…Though the velocity of air moving through the nasal passages is in fact time-varying, we assumed steady-state flow to match most previous work on the subject (e.g. [4][5][6][7][8][9][10]) and because good agreement exists between patterns of flow between steady and unsteady regimes [33].…”
Section: Methodsmentioning
confidence: 99%
“…dogs [3,5]; rats [6][7][8]), and those with a small olfactory region and poorly developed sense of smell on the other (e.g. humans [9,10]). To date, no study has attempted to use a group of closely related species to more precisely link differences in their apparent reliance on olfaction with differences in airway morphology and patterns of airflow.…”
Section: Introductionmentioning
confidence: 99%
“…Keyhani et al (1995) simulated the steady flow in the nose by the finite element method using FIDAP TM commercial software. Their 3D computational model for one of the nasal cavities from the nostril to the beginning of nasopharynx was constructed from the CAT scan sections of a human subject.…”
Section: Introductionmentioning
confidence: 99%